(untitled) (Journal of Educational Sciences, 2016)
Автор мақалада мектептің əлеуметтік-педагогикалық жұмыстар жүргізудегі негізгі орта екеніне тоқталады. Оқытудың оқушылар бойында танымдық жəне тəжірибелік жағымды мүмкіндіктер ашатынына көңіл бөлінеді. Training opens favorable possibility for in detail-practical and informative action of pupils. But with definition of perspective possibilities of pupils also come to light them. Priority directions of socialization. And how it occurs? In article we will try to clear up this question.